Experimental study of steel fiber concrete beams for shear, bending and torsion - Patil, Sudhir P.; Sangle, Keshav K. (Journal of Structural Engineering, 2025)
The low tensile strength and limited ductility, the unavoidable deficiency, of concrete can be overcome by the addition of fibers. In this research, an attempt was made to study the effects of fly ash and steel fibers on compressive, split tensile strength on concrete. The shear, flexural, and torsional strength of high strength plain and steel fiber concrete beam specimens. In this program, 99 cubes and 18 cylinder samples were casted for a trial mix design. The trial mixes were different percentages of fly ash and steel fibers. The concrete mixes had 10%, 20%, and 30% of fly ash by replacing cement to its weight and 0%, 0.5%, 1%, 1.5%, 2.0% and 2.5% of steel fibers by weight of cement concrete. The compressive strength of the fiber-reinforced concrete reached maximum at 20% fly ash and 1.5% volume fractions and the splitting tensile strength, and the modulus of rupture improved with an increasing volume fraction. To study flexural strength behavior, a total of 24 beam specimens of size 140x140x1500mm were casted having 12 beam specimens by adding 20% fly ash and 1.5% steel fiber, and 12 plain concrete beam specimens with 20% fly ash. A primary finding emerging from the experimental programme was that the placement of fibers, increased the load carrying capacity of reinforced concrete beam. Steel fiber reinforced concrete beam have enhanced ductility, shear, flexural, and torsional shear strength. All the specimens were tested for single, double point loading, pure torsion, combined bending, and torsion at the center after 28 days. The deflections were measured. The experimental and analytical results were compared.